2008
DOI: 10.2478/v10045-009-0001-1
|View full text |Cite
|
Sign up to set email alerts
|

A Pheromone-Based Trapping System for Monitoring the Population of Cosmopolites Sordidus (Germar) (Coleoptera: Curculionidae)

Abstract: Abstract:The banana root borer Cosmopolites sordidus (Coleoptera: Curculionidae) is native to Malaysia and Indonesia but is found in nearly all banana-growing areas of the world. Studies were conducted to determine the pheromone trap efficacy, effect of shade on trap catches and to monitor the population of C. sordidus using pheromones in Guam. In Guam, pheromone traps were used to monitor the population level of C. sordidus. Before monitoring began, two basic studies were carried out, which established that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 25 publications
(26 reference statements)
2
15
0
Order By: Relevance
“…The values recorded for the months of December, January and February were 175, 158 and 163, respectively ( Figure 2B). There was no significant correlation between the number of adults captured in the traps with rainfall, which contradicts the data obtained by Duyck et al (2012) and Price (1995) (Table 4), but partially corroborates the results of Reddy et al (2008) for nine of the ten locations evaluated in studies proving the efficiency of traps containing aggregation pheromone.…”
Section: Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…The values recorded for the months of December, January and February were 175, 158 and 163, respectively ( Figure 2B). There was no significant correlation between the number of adults captured in the traps with rainfall, which contradicts the data obtained by Duyck et al (2012) and Price (1995) (Table 4), but partially corroborates the results of Reddy et al (2008) for nine of the ten locations evaluated in studies proving the efficiency of traps containing aggregation pheromone.…”
Section: Resultssupporting
confidence: 45%
“…Therefore, this fact reinforces the need of banana weevil control, which might reduce disease spread. Some alternative methods have been evaluated for minimizing the economic damage posed by C. sordidus (Aby et al, 2015;Gold et al, 2001;Masanza et al, 2005;Reddy et al, 2008;Tinzaara et al, 2007;Uzakah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The data from our previous trapping studies indicated that a high population level (Ͼ10 per wk) was recorded in the northern region of Guam, whereas low (Ͻ5 weevils per wk) to medium (Þve to 10 weevils per wk) level populations occurred in the southern parts of the island (Reddy et al 2008). This weevil can cause a yield loss of up to 100% when left uncontrolled.…”
mentioning
confidence: 90%
“…Capture rates are higher during rainy periods (Pantoja et al, 2006;Reddy et al, 2008). The addition of pseudostem to pitfall traps does not significantly increase C. sordidus capture rates (Tinzaara et al, 2007a).…”
Section: Introductionmentioning
confidence: 92%
“…Several studies have confirmed the efficacy of sordidinbaited pitfall traps (Tinzaara et al, 1999;de Graaf et al, 2005). A more recent study demonstrated that crawl-in ground traps outperform pitfall traps (Reddy et al, 2009), and that traps are more effective in the shade (Reddy et al, 2008(Reddy et al, , 2009). Reddy's group also has shown that brown or black pitfall traps are more efficacious than other colors (Reddy and Raman, 2011).…”
Section: Introductionmentioning
confidence: 93%